EVALUATION OF THE SUCCESS OF IMPLEMENTING THE TAEKWONDO INDONESIA INTEGRATED SYSTEM APPLICATION USING THE HOT-FIT MODEL: CASE STUDY OF THE PROVINCIAL BOARD OF TAEKWONDO INDONESIA YOGYAKARTA - Suprianto, Suprianto; Paputungan, Irving V (Bakti Nusantara Institute, 2024)
Taekwondo Indonesia Integrated System is an application designed to manage various administrative and operational aspects related to the Taekwondo organization in Indonesia. Taekwondo Indonesia integrated system aims to improve coordination and communication between administrators, coaches, athletes, and members, as well as to ensure a more integrated and transparent administrative process at all levels of the organization. This research aims to evaluate the successful implementation of the Taekwondo Indonesia Integrated System using the HOT-Fit methodology. This research explores how various human, technological, and organizational aspects affect the success of the system. Data were collected through questionnaires measuring the dimensions of system quality, information quality, service quality, user satisfaction, system usage, organizational structure and net benefits, which were then analyzed using SPSS and PLS-SEM software. The results showed that service quality has a positive influence on user satisfaction, while system quality and information quality do not significantly affect user satisfaction or system usage. In addition, user satisfaction has a significant effect on system usage and net benefits, with organizational structure also playing a positive role in increasing net benefits. Improved service quality and a strong organizational structure are key to maximizing the success and benefits of the Taekwondo Indonesia Integrated System application. This research provides a practical contribution to the development and implementation of information systems in sports organizations, especially Taekwondo. In addition, the results of this study can be used as a basis for future improvements and enhancements to the TIIS application, so as to increase the efficiency and effectiveness of the operations of Taekwondo organizations in Indonesia.